New developments in the treatment of primary biliary cholangitis – role of obeticholic acid - Jhaveri MA; Kowdley KV (Dove Medical Press, 2017)
Manan A Jhaveri, Kris V Kowdley Liver Care Network, Swedish Medical Center, Seattle, WA, USA Abstract: Primary biliary cholangitis (PBC) is a chronic autoimmune cholestatic liver disease that predominantly affects women in early to middle age. It is typically associated with autoantibodies to mitochondrial antigens and results in immune-mediated destruction of small and medium-sized intrahepatic bile ducts leading to cholestasis, hepatic fibrosis and may progress to cirrhosis or hepatic failure and, in some cases, hepatocellular carcinoma. The clinical presentation and the natural history of PBC have improved over the years due to recognition of earlier widespread use of ursodeoxycholic acid (UDCA); about one-third of patients show suboptimal biochemical response to UDCA with poor prognosis. Until recently, UDCA was the only US Food and Drug Administration approved agent for this disease for more than two decades; obeticholic acid was approved in 2016 for treatment of patients with PBC with a suboptimal response or intolerance to UDCA. Currently, liver transplantation is the most effective treatment modality for PBC patients with end-stage liver disease. This review will focus on the recent advances in therapy of primary biliary cholangitis, with emphasis on obeticholic acid. Keywords: primary biliary cholangitis, obeticholic acid, ursodeoxycholic acid